Successful management of emphysematous prostatic abscess and concurrent liver abscess: A rare case report - Abdoulhafid Elmogassabi (17824223) (2023)
Emphysematous prostatic abscess (EPA) is a rare condition characterized by gas and abscess accumulation in the prostate. In this case report we report a successfully treated EPA with liver abscess due to Klebsiella pneumoniae in a 49-year-old man. He was admitted with abdominal pain and fever. Physical examination revealed tender, palpable resonance urinary bladder, and prostatic tenderness on rectal digital examination. High inflammatory markers were found. Abdominal computer tomography (CT) confirmed EPA. The patient was treated with broad-spectrum antibiotics, strict blood glucose control, suprapubic catheterization, and transurethral deroofing of the prostatic abscess. After three weeks patient discharged in good condition. Other Information Published in: Urology Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eucr.2023.102571